2012
DOI: 10.3126/hren.v10i3.7135
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in term labour with meconium stained amniotic fluid

Abstract: Introduction: Passage of meconium in utero is a dangerous sign for fetal outcome which influence the decision to deliver as well as the mode of delivery. Methods: This descriptive case control study was carried out in the department of Obstetrics and Gynaecology, Koshi Zonal Hospital from March 2006 to July 2006. A total of 50 women with meconium stained amniotic fluid( MSAF) were studied to identify maternal and fetal outcome and was compared with women with clear amniotic fluid. Results: Normal delivery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…It has been observed that obstetricians are more aggressive while managing labour with MSAF leading to high cesarean section rate, which was stastically significant in our study, more number of women with thick meconium underwent cesarean section as compared to thin meconium (60% vs 71%p-value 0.003). These findings are comparable with the study by Kumar S et al,14 in which cesarean delivery was higher 72% in thin meconium in contrast to thick meconium 21%. A possible explanation could be due to thick meconium occurring later in second stage.…”
Section: Discussionsupporting
confidence: 91%
“…It has been observed that obstetricians are more aggressive while managing labour with MSAF leading to high cesarean section rate, which was stastically significant in our study, more number of women with thick meconium underwent cesarean section as compared to thin meconium (60% vs 71%p-value 0.003). These findings are comparable with the study by Kumar S et al,14 in which cesarean delivery was higher 72% in thin meconium in contrast to thick meconium 21%. A possible explanation could be due to thick meconium occurring later in second stage.…”
Section: Discussionsupporting
confidence: 91%
“…There was an overall drop in the proportions of low Apgar scores from the 1st to [26] and by Rajlaxmi et al [27]. This high association of NNI and MSAF in our series could be explained by high proportions of prolonged premature rupture of membranes and resuscitation technics in the group with MSAF (p = 0.0047 and p = 0.0026 respectively).…”
Section: Discussionsupporting
confidence: 49%
“…The mean gestational age at delivery was significantly greater in the MSAF group as compared to the CAF group (39.7 weeks vs 39.2 weeks: P = 0.0001). Gestational ages ranging between 40 to 42 weeks was significantly more common in the MSAF group than the CAF group (41.78% vs 26.76%, p = 0.0011).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 92%
“…A study carried out by Gupta et al reported that 20% babies out of total 50 MAS cases developed hypoxic ischemic encephalopathy where 60% had thick meconium. 16 Another study conducted by Narang et al 6 reported that significant number of MAS cases (53.8%) developed birth asphyxia compared to those without MAS.…”
Section: Discusionmentioning
confidence: 96%
“…Although majority of babies with thick meconium had moderate respiratory distress (Downes` score: 4-6) at 12 hours and 24 hours from the time of admission but the difference was statistically not significant when compared in those with thin meconium. Gupta et al 16 showed that 20% of the babies had respiratory distress out of 50 babies delivered through meconium stained amniotic fluid with 21.4% having thick meconium. In a study conducted by Espinheira et al in 72 MAS babies, 11 (15.3%) were born asymptomatic whereas 61 (84.7%) had respiratory distress (mild, moderate and severe respiratory distress: 38.9%, 23.6% and 22.2% respectively).…”
Section: Discusionmentioning
confidence: 99%